Role of Production Area, Seasonality and Age of Fermented Camel (Camelus Dromedarius) Milk Gariss on Mineral Contents - Adam Ismail Ahmed; Babiker Elwasila Mohamed; Nuha Mohamed Elkhatim Yousif; Bernard Faye; Gerard Loiseau (Turkish Journal of Agriculture: Food Science and Technology, 2016)
The objective of this work was to study the differences between some minerals content of gariss samples collected from two different production areas in two different production systems (i.e. traditional system Kordofan area and semi-intensive system- which, the camels are kept in an open barn and graze around the farm. The lactating female camels are supplemented with concentrates in addition to good quality ration containing groundnut cake and Sorghum biocolor and water supply upon required in Kordofan and Khartoum provinces in Sudan at the different seasons (summer, autumn and winter) and their gariss samples were collected. Sodium, potassium, calcium, magnesium and phosphorus of gariss samples collected in autumn season (Kordofan area), summer season (Khartoum area), and winter season (Khartoum and Kordofan areas) were determined, after that the age of gariss was noted from farmers directly when the samples were collected. Four different ages of gariss which registered were (5-8 hrs, 12 hrs, 48 hrs and more than 48 hrs). Each fermentation time (age of gariss) was used for analyzing mineral contents. The results showed that gariss prepared from different production locations and in different seasons in Kordofan and Khartoum production areas were statistically different in most of the mineral contents determined. To conclude, different feeding sources or different physiological status may affect camels’ milk and consequently their gariss product, also different age of gariss had affects the mineral content of milk.